2007
DOI: 10.1002/fut.20259
|View full text |Cite
|
Sign up to set email alerts
|

The information content of option implied volatility surrounding the 1997 Hong Kong stock market crash

Abstract: This study examines the information conveyed by options and examines their implied volatility at the time of the 1997 Hong Kong stock market crash. The author determines the efficiency of implied volatility as a predictor of future volatility by comparing it to other leading indicator candidates. These include volume and open interest of index options and futures, as well as the arbitrage basis of index futures. Using monthly,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…It proves that the option trading volume can indeed reflect the future market volatility. The results coincide with the findings in Jayaraman et al (2001), Kawaller et al (2001), Poteshman (2006), andFung (2007). As the empirical results of the open interest are not the same as those of the option trading volume, the information covered in the option trading volume may have included the information set covered in the open interest.…”
Section: Inclusion Of the Option Market Informationsupporting
confidence: 80%
See 2 more Smart Citations
“…It proves that the option trading volume can indeed reflect the future market volatility. The results coincide with the findings in Jayaraman et al (2001), Kawaller et al (2001), Poteshman (2006), andFung (2007). As the empirical results of the open interest are not the same as those of the option trading volume, the information covered in the option trading volume may have included the information set covered in the open interest.…”
Section: Inclusion Of the Option Market Informationsupporting
confidence: 80%
“…On the contrary, if they predict future stock prices to be on the downward trend, they would tend to buy put options or sell call options in order to make profits. Jayaraman et al (2001), Kawaller et al (2001), Pand and Poteshman (2006), and Fung (2007) found that the trading volume and open interest of option markets possess the explanatory power regarding the future volatility of stock prices. The trading volume and open interest of option markets may reflect investors' expectations of future movement in stock markets.…”
Section: The Research Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with prior research in this area (e.g., Fung 2007;Taylor et al 2010), we use the following lead-lag regression model on our OTM put option price series for setup 1:…”
Section: Methodology: Revealing the Moderating Role Of Ambiguity (Setmentioning
confidence: 99%
“…Malz (2000) provided evidence that option-implied volatilities in a number of markets contain information about future large returns. Similarly, Fung (2007) found that option IVs gave an early warning sign and performed favorably compared to other measures in predicting future volatility during the 1997 Hong Kong stock market crash.…”
Section: Literaturementioning
confidence: 94%